LEGAL IMPLICATIONS OF THE CONSTITUTIONAL COURT'S DECISION TO ELIMINATE THE 20% PRESIDENTIAL THRESHOLD IN PRESIDENTIAL AND VICE-PRESIDENTIAL NOMINATIONS - Iman Nugraha; Andi Muhammad Asrun; Mustaqim (Awang Long Law Review, 2026)
This research aims to discuss the legal and political dynamics related to the 20% presidential threshold (PT) provision in Indonesia's presidential election system. PT is regulated in Article 222 of Law Number 7 of 2017 concerning General Elections, which has sparked much debate and legal challenges. The initial purpose of the PT was to strengthen the presidential system and simplify the number of presidential and vice-presidential candidates. However, its implementation is considered to hinder democratization and limit the people's political choices. Since its first implementation, the Constitutional Court has rejected various lawsuits seeking the cancelation of this provision, until finally, on January 2, 2025, the Court declared that PT 20% no longer has binding legal force. This research uses a normative-empirical approach and theories of democracy, the presidential system, and constitutional law. The research findings indicate that the Constitutional Court's change in attitude reflects a response to public pressure to create a more inclusive and democratic electoral system.